Syndecan Family Gene and Protein Expression and Their Prognostic Values for Prostate Cancer - Santos, Nilton José [UNESP]; Barquilha, Caroline Nascimento [UNESP]; Barbosa, Isabela Correa [UNESP]; Macedo, Rodrigo Tavares [UNESP]; Lima, Flávio Oliveira [UNESP]; Justulin, Luis Antônio [UNESP]; Barbosa, Guilherme Oliveira; Carvalho, Hernandes F.; Felisbino, Sérgio Luis [UNESP] (MDPI, 2021)
Prostate cancer (PCa) is the leading cause of cancer-associated mortality in men, and new biomarkers are still needed. The expression pattern and protein tissue localization of proteoglycans of the syndecan family (SDC 1-4) and syntenin-1 (SDCBP) were determined in normal and prostatic tumor tissue from two genetically engineered mouse models and human prostate tumors. Studies were validated using SDC 1-4 and SDCBP mRNA levels and patient survival data from The Cancer Genome Atlas and CamCAP databases. RNAseq showed increased expression of Sdc1 in Pb-Cre4/Ptenf/f mouse Pca and upregulation of Sdc3 expression and downregulation of Sdc2 and Sdc4 when compared to the normal prostatic tissue in Pb-Cre4/Trp53f/f-;Rb1f/f mouse tumors. These changes were confirmed by immunohistochemistry. In human PCa, SDC 1-4 and SDCBP immunostaining showed variable localization. Furthermore, Kaplan-Meier analysis showed that patients expressing SDC3 had shorter prostate-specific survival than those without SDC3 expression (log-rank test, p = 0.0047). Analysis of the MSKCC-derived expression showed that SDC1 and SDC3 overexpression is predictive of decreased biochemical recurrence-free survival (p = 0.0099 and p = 0.045, respectively), and SDC4 overexpression is predictive of increased biochemical recurrence-free survival (p = 0.035). SDC4 overexpression was associated with a better prognosis, while SDC1 and SDC3 were associated with more aggressive tumors and a worse prognosis.
Keywords: gene expression; outcome; prognostic marker; prostate cancer; survival; syndecan